Physics, asked by devanshpratapsingh65, 1 year ago

A wave represented by the equation y = acos(kx - wt) is superposed with another wave to form a stationary
wave such that the point x = 0 is a node. The equation for the other wave is
(2) -acos(kx + wt)
(1) asin(kx + wt)
(3) -acos(kx-wt)
(4) -asin(kx - wt)

Answers

Answered by sonuvuce
14

A wave represented by the equation y = acos(kx-ωt) is superimposed with another wave to form a stationary

wave such that the point x = 0 is a node. The equation for the other wave is -acos(kx + ωt)

Option (1) is correct.

Explanation:

The given wave equation:

y=a\cos(kx-\omega t)

It can be written as

y=a[\cos \omega t.\cos kx+\sin \omega t.\sin kx]

\implies y=a\cos \omega t.\cos kx+a\sin \omega t.\sin kx

If the superimposed wave has a node at x = 0 then the term containing cos kx should be zero

i.e. a\cos\omega t\cos kx should be zero

Thus, the other wave can have the equation of the form

y=-a\cos \omega t.\cos kx+a\sin \omega t.\sin kx

or, y=-a\cos(kx+\omega t)

Therefore, option (1) is correct.

Hope this answer is helpful.

Know More:

Q: To make a stationary wave having node at x = 0,  the equation y = Acos(wt + kx) is superimposed to  another wave of equation:

Click Here: https://brainly.in/question/14378591

Q: Two waves represented by y= a sin(wt - kx) and y= a cos(wt - kx) are superposed The resultant wave will have an amplitude:

Click Here: https://brainly.in/question/2764498

Similar questions